Sounding emerging media - Fitch, Claire (Routledge, 2022)
"Sounding Emerging Media details a practice-based approach to sonic art and electroacoustic composition, drawing on methodologies inspired by the production of electronic literature, and game development. Using the structural concepts identified by Gilles Deleuze and Fľix Guattari, the book is based around ideas related to labels such as Assemblage, Strata, Smooth and Striated Space, Temporal Space and, The Fold. The processes employed to undertake this research involved the creation of original texts, the development of frameworks for improvisation, the use of recordings within the process and implementation of techniques drawn from the practices of electroacoustic composition, and the use of ideas borrowed from electronic literature, publishing and game development. The results have helped to shape a compositional style which draws on these processes individually or collectively, drawing on practice often seen in game development, visual scores and composition using techniques found in electroacoustic music. Providing a journey through the landscape of emerging digital media, Sounding Emerging Media envisages a world where the composer/user/listener all become part of a continuum of collective artistry. This book is the ideal guide to the history and creation of audio for innovative digital media formats and represents crucial reading for both students and practitioners, from aspiring composers to experienced professionals"--